Perbedaan Jumlah Eritrosit Antara Darah Segar dan Darah Simpan - Rizki Arviananta; Syuhada Syuhada; Aditya Aditya (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
At the time of collection of blood, donor erythrocytes will experience damaged, every day the viability of erythrocytes continues to decrease due to decreased levels of ATP (Adenosine Triphosphate), so that when ATP levels decrease then there is the loss of membrane lipids, the membrane becomes rigid every day, and the shape of the disc becomes spherical (without central polar and small size), this causes potassium to exit and sodium to enter the cell. Then this will affect erythrocytes amount to be transfused. This study aimed to determine the differences in erythrocytes amount between fresh blood and save blood (30 days. The type of research used is Quantitative Observational with Non-probability Sampling technique. The sample used in this study were research subject who were willing to donate blood. Analysis of data using the Wilcoxon formula. Based on the results of the examination, the mean reduction in erythrocyte amount for 30 days at men was 4.624 million/mm3 (9.3%) and at women 3.88 million/mm3 (8.2%), where the decrease was still within the normal limit. Obtained p-value > 0,05 which means there is no significant difference in erythrocytes amount between fresh blood and save blood (30 days).